(E)MERGING DISCOURSES: ARCHITECTURE AND CULTURAL STUDIES - McGaughey, Sarah (Imaginations: Journal of Cross-Cultural Image Studies, 2012)
Three recent works, Rosalind Galt’s Pretty, Anne Cheng’s Second Skin, and Daniel Purdy’s On the Ruins of Babel incorporate architectural history and architectural discourse into their analyses in ways that are new to their respective fields ranging from studies of film, gender, and race to intellectual history. Placing these three works in one essay allows for a detailed review of the ways in which each author employs architecture, at the same time as it reveals the benefits and challenges of incorporating architecture into cultural studies. The essay discusses the contributions of each work to their fields and also takes advantage of the different approaches to culture and architecture to explore the ways in which this relationship might continue to inform and generate productive studies.